Long term measurements of neutron dose rates at Testa Grigia high altitude research station (3480 m. a.s.l.). (April 2022) - Vernetto, S.; Laurenza, M.; Storini, M.; Zanini, A.; Diego, P.; Massetti, S.; Liberatore, A.; Terrazas, J.C.; Vigorito, C.; Vallania, P.; Cirilli, S.
Abstract: At the Testa Grigia high altitude research Station (3480 m. a.s.l, Italy, 45°57′ N, 7°42' E) several dosimetric campaigns for the measurement of the dose due to secondary neutrons produced in the atmosphere and in the surrounding environment by primary cosmic rays have been carried out from 2014 until 2021. Because of the high altitude of the site, the neutron flux at Testa Grigia is 10–15 times higher than at the sea level. Various instruments has been used to evaluate the dependence of the ambient dose equivalent rate from different factors as atmospheric parameters, environmental conditions and solar activity. Moreover, since October 2014 a modular neutron monitor designed, realized and tested by the SVIRCO Observatory Group INAF-IAPS in Rome, is permanently operating in the laboratory, providing a continuous monitoring of primary cosmic ray variability and making the laboratory an ideal place for dosimetric studies, instrument calibration and "in field" tests. In this paper the results of several neutron measurements carried out in the last years in periods of different solar activity and environmental conditions are reported, with a discussion on the origin of the observed variations of the ambient dose equivalent rate. Highlights: The dose rate due to secondary cosmic rays neutrons is monitored at the Testa Grigia Laboratory. Neutron dose rate variations are studied in different environmental conditions. The sensitivity of different neutron detectors to neutron flux variations is studied.